Pre-transplant thrombocytopenia predicts engraftment time and blood products requirement in allogeneic hematopoietic stem cell transplantation patients. (August 2020) - Roshandel, Elham; Kaviani, Saeid; Hajifathali, Abbas; Soleimani, Masoud
Abstract: Introduction: Thrombocytopenia is a common consequence of leukemia that affects the outcome of hematopoietic stem cell transplantation (HSCT). The stromal damage of bone marrow following pre-HSCT conditioning regimens can delay the hematopoietic engraftment and increased blood product transfusions. We tried to define threshold based on pre-transplant platelet count as a biomarker to predict engraftment time and blood product requirements in allogeneic HSCT patients. Methods: This retrospective study was performed on 194 patients who received allogeneic HSCT. The median for platelet (PLT) count of patients at the admission day was considered as a cut off value. The association of platelet count with white blood cell (WBC) and PLT engraftment time and also the requirement of packed red blood cell or PLT transfusions as outcomes of interest were investigated. Results: 164 patients (84.5 %) had successful WBC engraftment, and PLT engraftment was seen in 155 patients (79.9 %) in 30 and 50 days after HSCT, respectively. The patients with PLT count higher than 154, 000/μL had better PLT engraftment (P = 0.060), and WBC engraftment (P = 0.014) than those with PLT count lower than this cut off. The pre-transplant PLT count had negative relations with SD platelet requests after HSCT (P = 0.008). Conclusion: The thrombocytopenia before HSCT might delay the platelet and WBC engraftment time, which should be taken into account before transplantation. Since the blood product transfusion is one of the factors associated with engraftment, the pre-transplant platelet count can be used as a predictive biomarker to manage the blood product requirement during the HSCT until engraftment occurs.